Além do UM e da ciência do espaço do homem : Interlocução com a coexistência de todas as formas de vida em e do(s) espaço(s) - Arias, Leonarda Paola de La Ossa (2019)
In this dissertation, I intend to question and interlocute, based on the Pu1 Mapuche spatial practices, the ontological difference / conflict / misunderstanding in the relationship of the indigenous people with the Chilean nation-state; from the resumption of the concept of coexistence of different forms of life, which emerges in the spatial statements Pu Mapuche, analyzing from the perspective of the ontology of the geographical space (Tosta, 2012) the route and the emergence of the statements of geographical space land, territory and territoriality, as concepts and practices, built since the relations with the Crown of Spain, in the process of colonial expansion. I look at the Pu Mapuche concepts of geographical space, land, territory and territoriality, which are related to those of history, memory and time, and which are put in tension in the judicial space. The dissertation proposes the concept of the judicial space, which emerges as an unfolding in the framework of production in the capitalist flows of the geographical space, and is present not in the representations of the geographical space, but in the concrete spatial practices: tensions, conflicts and mistakes of an ontological nature , which the present dissertation addresses through the provocations coming from different currents, and which have converged mainly in the so-called Radical Critical Geography or is in itself a new (other) radical criticism, coming from Amerindian peoples to the so-called Modern Geography. The dissertation makes notes about the Mapuche spatial conception, which refers, not to the production of space, but suggests a construction (Quidel 2012; Becerra et al, 2017) or, more specifically, construction acts, in Longko's proposal Mapuche anthropologist, José Quidel (2012, p.81). However, I return to Pu Mapuche's historiographical narrative and spatial practices and statements about ethnocide, involving several geographical concepts that can provide key elements for understanding the process of “construction” of space, in the context of what Pu Mapuche claim as spaces ancestors. This look gives the possibility to analyze, in the key of the cosmopolitical proposals (Stengers, 1997; Schavelzon, 2016; Viveiros De Castro, 2002; 2010; Valentim, 2018), which could be considered, in Pu Mapuche's own terms, the inclusion from the Mapu perspective to politics (Quidel, 2012; Melin et al, 2017), creating Pu Mapuche's own strategies and rights to face tensions with the nation-state. In this process, concepts such as Rakizuam (thought), Az Mapu (proper order), Kvme Mogen (form of life / good living) and Kisugünewi (self-government) emerge. Thus, I resort to an ethnographic work of what I have called the judicial space, specifically the Courts and Judgments, in which tensions play a role as a witness to the wounds still open, the continuity of the colonization process and ethnocide, which I study based on the proposals made by (Clastres, [1980] 2011); Melin et al, 2015; Melin et al, 2017; Melin and Mansilla, 2019), reformulated in their own terms by Pu Mapuche since and in dialogue with many sciences: Anthropology, History, Sociology and Pedagogy, but reaffirming the Mapu perspective as a spatial perspective that reaffirms and positions itself as a new or another (s) geographies of life, which, above all, defend the coexistence of different and all forms of life as an imperative and ontological determinant, in contrast to the ontological shares of the so-called Modern Geographic Thought related to nature and culture.